1979
DOI: 10.1139/m79-109
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of sea water–urea as a culture medium for Spirulina maxima

Abstract: The possibilities of utilization of seawater enriched with ureas as the culture medium for a blue-green alga, Spirulina maxima, were investigated. Pretreatment by precipitation with NaHCO3 and (or) Na2CO3 was found essential to remove the excess amounts of Ca2+ and Mg2+ present in seawater prior to cultivation. A culture medium as good as the synthetic medium reported in the literature for the growth of S. maxima was obtained after treating seawater with NaHCO3 (19.2 g/L) at pH 9.2 and 35 degrees C for 2 h, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

1982
1982
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…The P88 strain did not show significantly differences in the treatments in relation to the white (P > 0.05). Similar results were gotten by Faucher et al (1979) and Mary Leema et al (2010) who have reported growing rates comparable or superior to the white medium or control (standard mineral medium) for A. platensis maximum growth in sea water supplemented with phosphorus and nitrate and addition to the A. platensis have shown that external concentrations of sea salt of up to 150% in seawater had little effect on the A. platensis strain growth (Warr et al 1985). According to these researchers the capacity of A. platensis to tolerate high salinity levels seems to be an important factor that allows it to survive and to grow in lakes and other similar alkaline brackish water.…”
supporting
confidence: 84%
“…The P88 strain did not show significantly differences in the treatments in relation to the white (P > 0.05). Similar results were gotten by Faucher et al (1979) and Mary Leema et al (2010) who have reported growing rates comparable or superior to the white medium or control (standard mineral medium) for A. platensis maximum growth in sea water supplemented with phosphorus and nitrate and addition to the A. platensis have shown that external concentrations of sea salt of up to 150% in seawater had little effect on the A. platensis strain growth (Warr et al 1985). According to these researchers the capacity of A. platensis to tolerate high salinity levels seems to be an important factor that allows it to survive and to grow in lakes and other similar alkaline brackish water.…”
supporting
confidence: 84%
“…Considering the nutritive value of Spirulina and the obvious ease of its harvesting, the alga has been the subject of a number of mass culture studies in several countries 8,11,12,16,18,21,22,25,26. At present, an industrial pilot plant in Mexico produces one ton of S. maxima biomass per day 13.…”
mentioning
confidence: 99%
“…In addition, large‐scale production of microalgae was realized in open‐pond system on earth, promoting the use of microalgae in industry . Importantly, researchers tried to replace artificial medium by seawater or waste stream, thus, extending the use of microalgae from air revitalization and food supply to wastes remediation 1980s: Advanced bioreactors for algae cultivation A variety of closed photobioreactors, which can regulate the mixing speed, temperature, and gas concentration, were designed and used for microalgae production .…”
Section: Development Paths Of Microalgae‐based Blssmentioning
confidence: 99%